Thymus vulgaris Essential Oil in Beta-Cyclodextrin for Solid-State Pharmaceutical Applications - Aldo Arrais; Elisa Bona; Valeria Todeschini; Alice Caramaschi; Nadia Massa; Maddalena Roncoli; Alessia Minervi; Elena Perin; Valentina Gianotti (MDPI AG, 2023)
Antimicrobial resistance related to the misuse of antibiotics is a well-known current topic. Their excessive use in several fields has led to enormous selective pressure on pathogenic and commensal bacteria, driving the evolution of antimicrobial resistance genes with severe impacts on human health. Among all the possible strategies, a viable one could be the development of medical features that employ essential oils (EOs), complex natural mixtures extracted from different plant organs, rich in organic compounds showing, among others, antiseptic properties. In this work, green extracted essential oil of Thymus vulgaris was included in cyclic oligosaccharides cyclodextrins (CD) and prepared in the form of tablets. This essential oil has been shown to have a strong transversal efficacy both as an antifungal and as an antibacterial agent. Its inclusion allows its effective use because an extension of the exposure time to the active compounds is obtained and, therefore, a more marked efficacy, especially against biofilm-producing microorganisms such as P. aeruginosa and S. aureus, was registered. The efficacy of the tablet against candidiasis opens their possible use as a chewable tablet against oral candidiasis and as a vaginal tablet against vaginal candidiasis. Moreover, the registered wide efficacy is even more positive since the proposed approach can be defined as effective, safe, and green. In fact, the natural mixture of the essential oil is produced by the steam current method; therefore, the manufacturer employs substances that are not harmful, with very low production and management costs.